The role of growth mindset, self-efficacy and intrinsic value in self-regulated learning and English language learning achievements - Bai, Barry; Wang, Jing (Language teaching research : LTR, 2023)
This study examined the role of growth mindset, self-efficacy, and intrinsic value in self-regulated learning (SRL) and English language learning achievements in Hong Kong primary school students. A sample of 690 4th graders participated in the study. The findings suggest that the level of SRL strategy use (i.e. monitoring, effort regulation, and goal setting and planning) was driven by the students’ motivational beliefs (i.e. growth mindset, self-efficacy, and intrinsic value) in different ways. Monitoring and effort regulation, in turn, were significant contributors to the participants’ English language learning achievements, but goal setting and planning did not predict their English language learning achievements. The finding suggests that growth mindset was a stronger predictor of SRL than self-efficacy and intrinsic value. Implications for fostering adaptive motivational beliefs and SRL are discussed. Future research should consider the influence of the socio-cultural context on the relationships between motivational factors, SRL strategy use, and English language learning achievements.